2015
DOI: 10.1007/s40670-015-0161-3
|View full text |Cite
|
Sign up to set email alerts
|

Integration and Improvement of Teamwork Skills in First Year Medical Students by Using Physiology-Based High Fidelity Patient Simulations

Abstract: Communication errors between team members underlie many of the preventable patient errors within the US healthcare system. Medical students do not get the opportunity to take advantage of TeamSTEPPS® training because they are not consistently a part of hospital-based teams. Most of their communication skills training are focused on the doctor and patient relationship and less focus on teamwork (TW) skills. Developing TW skills earlier in medical education may help lead to better communication and patient safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…In our Table 2. Comparison of median ratings for each observation from all of the groups' first and last simulation HFPS, the second part of each debriefing session focuses on group dynamics to address some of these concerns, as past studies have shown that group dynamics can improve over series of HFPS, if these are included as a topic in debriefs (27). For this study, the initial discussion of teamwork skills was addressed after the first simulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our Table 2. Comparison of median ratings for each observation from all of the groups' first and last simulation HFPS, the second part of each debriefing session focuses on group dynamics to address some of these concerns, as past studies have shown that group dynamics can improve over series of HFPS, if these are included as a topic in debriefs (27). For this study, the initial discussion of teamwork skills was addressed after the first simulation.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, the initial discussion of teamwork skills was addressed after the first simulation. Therefore, as students improve teamwork skills, it is possible that this could also contribute to improved scores on the CTSRI (27). Further studies are still necessary to look at group interaction and the role it plays in the group thought process.…”
Section: Discussionmentioning
confidence: 99%